2009
DOI: 10.1212/01.wnl.0000341276.65721.f2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing explorative saccade and flicker training in hemianopia

Abstract: Explorative saccade training selectively improves saccadic behavior, natural search, and scene exploration on the blind side. Flicker-stimulation training does not improve saccadic behavior or visual fields. The findings show substantial benefits of compensatory exploration training, including subjective improvements in mastering daily-life activities, in a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
115
1
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 38 publications
9
115
1
9
Order By: Relevance
“…This improved visual search is likely to be an important factor in the adaptation process, and this theory has been explored by Roth et al. (2009) in that their study showed explorative saccadic training to improve saccadic behavior, search skills, and scene exploration on the hemianopic side, showing benefits of compensatory exploration training which are transferable to everyday tasks. The interventions targeted by these strategies will be discussed in more detail in the second section of this review.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…This improved visual search is likely to be an important factor in the adaptation process, and this theory has been explored by Roth et al. (2009) in that their study showed explorative saccadic training to improve saccadic behavior, search skills, and scene exploration on the hemianopic side, showing benefits of compensatory exploration training which are transferable to everyday tasks. The interventions targeted by these strategies will be discussed in more detail in the second section of this review.…”
Section: Resultsmentioning
confidence: 97%
“…The development of adaptive eye movement strategies over time has been well documented, and the implication of these compensation strategies is that subjects develop a more effective visual search technique, for a variety of tasks such as obstacle avoidance and driving (Hardiess et al., 2010; Meienberg et al., 1981; Machner et al., 2009; McDonald et al., 2006; Pambakian et al., 2000; Papageorgiou, Hardiess, Mallot, & Schiefer, 2012; Zangemeister & Oechsner, 1996; Wood et al., 2011; Roth et al., 2009). This improved visual search is likely to be an important factor in the adaptation process, and this theory has been explored by Roth et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional ability in performing activities of daily living was used as a primary outcome measure. Thirteen trials were identified as meeting the inclusion criteria (Bainbridge & Reding, 1994; Carter, Howard, & O'Neil, 1983; Jobke, Kasten, & Sabel, 2009; Kasten, Bunzenthal, Muller‐Oehring, Mueller, & Sabel, 2007; Kasten, Wurst, Behrens‐Baumen, & Sabel, 1998; Plow et al., 2010; Poggel, Kasten, & Sabel, 2004; Rossi, Kheyfets, & Reding, 1990; Roth et al., 2009; Spitzyna et al., 2007; Szlyk, Seiple, Stelmack, & McMahon, 2005; Weinberg et al., 1977, 1979). Limited meta‐analyses were possible and were only completed for compensatory interventions.…”
Section: Interventionsmentioning
confidence: 99%